A new cytokine‐based dynamic stratification during induction is highly predictive of survivals in acute myeloid leukemia. (25th December 2020) - Peterlin, Pierre; Gaschet, Joelle; Guillaume, Thierry; Garnier, Alice; Eveillard, Marion; Le Bourgeois, Amandine; Cherel, Michel; Debord, Camille; Le Bris, Yannick; Theisen, Olivier; Godon, Catherine; Mahé, Béatrice; et al.
Abstract: The aim of this study was to assess the potential impact of the kinetics of serum levels of seven cytokines during induction in acute myeloid leukemia (AML) patients. Indeed, the role of cytokines, in the pathophysiology and response to therapy of AML patients, remains under investigation. Here, we report on the impact of peripheral levels of two cytokines, the Fms‐like tyrosine kinase 3 ligand (FL) and interleukin‐6 (IL‐6), evaluated during first‐line intensive induction. A new risk stratification can be proposed, which supersedes the ELN 2017 classification to predict survivals in AML patients by examining the kinetic profile of these cytokines during the induction phase. It segregates three groups of, respectively, high‐risk, characterized by a stagnation of low FL levels, intermediate risk, with dynamic increasing FL levels and high IL‐6 at day 22, and favorable risk with increasing FL levels but low IL‐6 at day 22. Abstract : Here we report on the impact of the peripheral levels of two cytokines, the Fms‐like tyrosine kinase 3 ligand (FL), and interleukin‐6 (IL‐6), evaluated during first‐line intensive induction. Indeed, a new risk stratification can be proposed, which supersedes the ELN 2017 classification to predict survivals in AML patients by examining their profile during the induction phase.